Covid-19 outbreak response: Tracing EFL teachers’ beliefs & practices of TPACK in teaching writing - Lailatun Nurul Aniq; Nur Arifah Drajati; Endang Fauziati (Universitas Pendidikan Indonesia, 2022)
Little is recognized regarding teachers’ beliefs about teaching with the appropriate framework integrating technology into language instruction, particularly during the COVID-19 outbreak. TPACK is a framework for apprehending knowledge domains required by EFL teachers nowadays. The preliminary study indicated that among the four English skills taught to middle school students, teaching writing was the most challenging. Therefore, it is essential to understand more about teachers’ beliefs regarding the practice of the TPACK framework in teaching writing. For that reason, This study aimed to (1) explore teachers' beliefs about the TPACK framework and (2) analyze classroom practices in teaching writing. This case study examined three teachers from different senior high schools in Indonesia of their beliefs about teaching writing with the TPACK framework and their classroom practices. A semi-structured interview was administered to explore their beliefs, while classroom observations focused on their classroom practices. The results demonstrated similarities and differences among teachers’ beliefs about learning objectives, teacher’s role, and assessment, while in classroom procedure and instructional material, teachers shared identical beliefs. Indeed, there was a majority of consistency between teachers’ beliefs and classroom practices of teaching writing with the TPACK framework. Despite its paramount consistency between teachers’ beliefs and classroom practices, the presence of the government to educate teachers is urgently needed, which can be in the form of virtual TPACK training. Then, this study may provide references for teaching writing with the TPACK framework that can adequately be applied during the COVID-19 outbreak and new normal.